Estilos de vida y su influencia en el deterioro motor de los adultos mayores que acuden al Centro de Salud Enrique Ponce Luque, periodo junio – octubre 2023 - Arguello Acosta, Alinson Lisbeth (2023)
Gerontological nursing has evolved from an experience-based practice to a profession with solid scientific foundations, supported by research, specialized education, and a comprehensive focus on the needs of older adults. This evolution has made it possible to provide more effective and high-quality care to this growing population. There are several risk factors such as a sedentary lifestyle, decreased physical exercise, chronic diseases, protein deficiency or malnutrition, metabolic alterations and the use of drugs that cause motor deterioration to decrease more quickly in older adults. For these reasons, this research is carried out to impart our knowledge for the benefit of older adults who present motor impairment, they usually have a combination of muscle weakness, loss of muscle mass (sarcopenia), decreased walking speed, fatigue, low resistance and a greater susceptibility to changes in your health status. Treatment and management of motor impairment depends on the underlying cause. They may include physical therapies, rehabilitative exercises, medications, assistive devices, and lifestyle changes. In some cases, motor impairment may be irreversible, but with appropriate interventions, affected individuals can improve their quality of life and functional capacity.